Sistematização dos microprocessos da capacidade absortiva para identificação do conhecimento em gestão de projetos - Moraes, Alan Tadeu de (2019)
The area of Project Management has evolved a lot in regard to ways of managing knowledge. The complexity of the projects and the temporal aspect related to the establishment of the beginning, middle and end process presents the challenge that knowledge does not get lost in its life cycle. The Knowledge Management process can be understood as a way of acquiring competitive advantage by means of a better organization of knowledge management. Once the studies have evolved into increasingly comprehensive models such as the spiral of knowledge, which considers the epistemological and ontological dimensions at the various levels of an organization, as well as contributes to the knowledge management (CG) to bring a competitive advantage to organizations. An analysis of these studies showed that the knowledge identification phase did not consider how the process of knowledge identification takes place. Thus, this study aims to describe how the microprocesses of the Absorptive Capacity acquisition phase contributes to the identification of knowledge in project management. To this end, an exploratory and descriptive qualitative research was adopted, with 15 in-depth interviews with professionals who have more than 05 (five) years of experience with projects. In the interviews microprocesses were identified in the phase of acquisition of Absorptive Capacity that contributes to the knowledge identification knowledge in Project Management. These microprocesses were grouped into three categories called (i) events, (ii) social interaction and (iii) use of tools and techniques. As contributions, besides the microprocesses identified in the practices reported by the interviewees, this study presents a systematization of how the knowledge identification occurs in the context of project management, which allows organizations to intervene in their processes and activities with the microprocess that best fit them to the reality of projects according to their complexity, criticality or innovation.